(3OQGSI MGdI JhfS, GdLRGFQ, GdeZQH CfehPLGs - (3HhMfjI (B, (3bhis; (3QeVGf(B, (3YHO GdeLjOs ((3YeGf(B:s (3OGQ MGeO ddfTQ hGdJhRjY(B,s, 2018)
(3jQcR ehVhY YPG GdcJGH Ydi OQGSI QDj GdfXe GdSjGSjI aj GdOhd GdeZGQHjI dSHd EUdGM GdEOGQI GdeMdjI hJLGhR fbGFU JLGQH GdOjebQGWjI GdJeKjHjI Yf WQjb JHfj NjGQ GdOjebQGWjI GdJTGQcjI, hGdHMK Yf GdBdjGJ GdcajdI HVeGf JWHjb hJaYjd GdGTQGc GdSjGSj ddehGWfjf, OYeG dacQI GdJSjjQ GdLeGYS dTDhf GdLeGYI GdeMdjI(B.s
Keywords: (3GdEUdGMGJ GdSjGSjI hGdEOGQjIs; (3GdOjebQGWjIs; (3GdOjebQGWjI GdJTGQcjIs